A new distributional range of Abraxas antipusilla Inoue, 1995 (Lepidoptera: Geometridae) from Eastern Himalaya, India - Gayen, Subrata; Chandra, Kailash (Zootaxa, 2023)
Based on Indian Himalayan expeditions, the species Abraxas antipusilla Inoue, 1995 is reported for the first time from Eastern Himalaya, India. After two decades, differential diagnoses of males and females are presented in comparison to Abraxas pusilla Butler, 1880. Redescriptions of male and female genitalia are given. An annotated summary on habitat preference and distributional ranges for both species is emphasized within the Indian Himalayan Region.